RULES OF ORIGIN SEBAGAI INSTRUMEN PENANGANAN PRAKTIK ILLEGAL TRANSHIPMENT - Esty Hayu Dewanty R.K. (Yuridika, 2012)
The influence of globalization has become wider and it caused the increasing of intensity of world’s trade between countries. However, this positive development is followed by a lot of fraudulent in international trading such as Illegal Transhipment, whereas a country exports to other countries through the third country by some methods. Indonesia, as an active member of international trade forums, is also threaten to be one of the victim of Illegal Transhipment, by the method of Certificate of Origin. If it’s allowed, Indonesian’s traders will suffer financial loss and also will interfere with national economic stabilization. Rules of Origin on the Certificate of Origin is one of indicator of Illegal Transhipment and can be used as the reference of trade’s policy to give back national economic loss. Therefore, preventive and repressive handling of Illegal Transhipment through Rules of Origin is needed to be done.Keywords : Rules of Origin, Certificate of Origin, Illegal Transhipmen